Construcción de identidad de las personas refugiadas en situación de movilidad humana en el barrio "Las Tolas" de la ciudad de Quito - Fonseca Hurtado, Karina Soledad (2015)
Identity is a set of elements; customs, traditions, symbols, rituals. Other transmitted and socially shared, which allows us to identify and differentiate between them represents who we are, where we came allows us to build a sense of belonging, connect with our history, our origins, in other words the identity entails that we can recognize ourselves as subjects of a society. From this perspective people as refugees in situations of human mobility, to be forced to leave its territory, leaving behind part of their identity, they create identities which subjectivities related to the new reality we are forced to live through adaptation strategies and differentiation in various sociocultural systems established in the host country, within a new society, largely hostile and discriminating has established strategies of exclusion based on negative stereotypes that limit proper integration social of people as refugees. In response, the refugee populations have been found in the need for support networks and generate points of visibility and social representation supported in symbolic spaces that allow the refugee / a bond with their identity within a foreign country. The refugees are forced to leave their home people leave their families, friends, violently; many of then come to Ecuador with nothing but all with the hope to live in peace.